TOKENIZATION AS A DETERMINANT OF THE DEVELOPMENT OF NEW TECHNOLOGIES (Research Bulletins of the Faculty of Economic Sciences, 2023)
The aim of this paper is to characterize and present the essence of tokens that are digital value carriers of goods and services, as well as tokenization and tokenomics developed on it. The article is a review with emphasis on explaining these three concepts and indicating the possibility of their application in practice. The study formulated the following research problem: whether, and if so, how tokenization can be used in the modern world. In order to find an answer to this question, the method of source analysis and criticism, the case study method and the deductive method were used.
Keywords: token, tokenization, tokenomics, blokchain, technology